Copper(i) targeting in the Alzheimer's disease context: a first example using the biocompatible PTA ligand1. Issue 8 (5th August 2015) - Atrián-Blasco, E.; Cerrada, E.; Conte-Daban, A.; Testemale, D.; Faller, P.; Laguna, M.; Hureau, C.
<x xml:space="preserve">Abstract</x> The use of a Cu(i) stabilizing ligand to target copper ions is a very promising approach against Alzheimer's disease.